2009
DOI: 10.4102/curationis.v32i2.924
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the meaning of integrated Primary Health Care from the KwaZulu- Natal Primary Health Care context

Abstract: In South Africa, integration o f services policy was enacted in 1996 with the aim of increasing health service utilization by increasing accessibility and availability of all health care services at Primary Health Care (PHC) level. Integration of PHC services continues to be seen as a pivotal strategy towards the achievement of the national goals of transformation of health services, and the attainment of a comprehensive and seamless public health system. Although the drive behind the integration of PHC servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…A one-stop-shop approach to care, where mental health care users are managed holistically by one nurse, was reported to take place in clinics where their PHC nurses had a qualification in psychiatric nursing. The results of this study are consistent with the findings of the study that was conducted by Sibiya and Gwele, 22 who found that IPHC was viewed by participants as the provision of services by one nurse and that the patient receives comprehensive care in one clinic. In South Africa, PHC comprehensive package indicates that clinics should provide comprehensive IPHC service through a one-stop-shop approach for a minimum number of hours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A one-stop-shop approach to care, where mental health care users are managed holistically by one nurse, was reported to take place in clinics where their PHC nurses had a qualification in psychiatric nursing. The results of this study are consistent with the findings of the study that was conducted by Sibiya and Gwele, 22 who found that IPHC was viewed by participants as the provision of services by one nurse and that the patient receives comprehensive care in one clinic. In South Africa, PHC comprehensive package indicates that clinics should provide comprehensive IPHC service through a one-stop-shop approach for a minimum number of hours.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, a one-stop-shop approach may result in staff being overloaded with work. 23 Sibiya and Gwele 22 argue that one can never be sure if a one-stop-shop approach saves time or not and further state that it may take longer for one nurse to provide all the services.…”
Section: Discussionmentioning
confidence: 99%
“…Uebel et al ( 2013a :9) reported that models of integration for HIV care ‘varied on a spectrum from a fully integrated service, where patients accessed HIV care from any nurse, to a more separate delivery of care, with patients accessing care from a specific ART nurse’. Sibiya and Gwele ( 2009 :35) describe integrated comprehensive PHC services as a supermarket or one-stop approach. For the purpose of this report the NDOH's (2012b:9) definition of ‘integration’ will be used, referring to a ‘one-stop shop under one roof’ service to ensure comprehensive health care services to patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study on students' perceptions of the applicability of the PHC approach in the South African context, revealed that students were of the view that the PHC principles could not be applied in the country, given its poor socio-economic situation primarily in the rural areas [9]. A study which came very close to our study was conducted by Sibiya and Gwele in KwaZulu Natal in 2009, who analysed the meaning of integrated PHC among policy makers and coordinators of PHC at national, provincial and district levels, including PHC nurses at healthcare facility level [10]. One of the questions the participants were asked enquired on what they understood by "integrated PHC," and the study ndings were that PHC was conceptualised as comprehensive health care, employing a "supermarket" and a "one stop shop" approach in health care delivery [10].…”
Section: Introductionmentioning
confidence: 75%